Determination of the fetus gender in the light of Quran - Abdul Rahman Hussein Obeid; Mohd Zohdi Mohd Amin; Syed Ahmad Tarmizi Syed Omar; Adnan Mohamed Yusoff; Abdullaah Jalil; Robiatul Adawiyah Mohd @ Amat; Norazman Alias; Tazul Islam; Zamrie Ibrahim @ Musa; Mohammed Akhiruddin Ibrahim; Khairul Anuar Mohamad; Kauthar Abd Kadir; et al. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA